Alur Pendaftaran Calon Mahasiswa Baru Politeknik Sekayu Berbasis Multimedia - Zaid Romegar Mair; Yuni Kartika (Jurnal Nasional Ilmu Komputer, 2021)
Multimedia is one form of information technology, namely information technology that combines images, writing, text, sound, video, animation into an information system that is useful in making decisions for its users. This media displays information about the registration flow of prospective new students in a clear and concise manner. The method used is the MDLC (Multimedia Development Life Cycle) method as software development. For an explanation of each registration flow information using audio, in addition to making this media more interesting, characters or animations are displayed.